The endothelin axis in head and neck cancer: a promising therapeutic opportunity?. (20th August 2013) - McKenzie, Gordon A. G.; Hinsley, Emma E.; Hunter, Keith; Lambert, Daniel W.
<x xml:space="preserve">Abstract</x> The incidence of head and neck cancer, predominantly consisting of squamous cell carcinomas (HNSCCs), is continuing to rise worldwide. Invasive HNSCC carries a poor prognosis, and the detrimental sequelae of surgical resection motivate identification of novel modes of therapeutic intervention. The endothelin (ET) axis consists of ET‐1, 2 and 3, which are generated by endothelin‐converting enzyme (ECE) and engage with the receptors ETAR and ETBR. The ET axis plays a role in the development and progression of various human malignancies. ET axis components have been found to be overexpressed in HNSCC; ET‐1 antagonism and inhibition of ECE may therefore represent viable therapeutic opportunities. ET‐1 can promote HNSCC progression via stromal–epithelial interactions, suggesting that the stroma may also hold potential for therapies targeting components of the ET axis. The ET axis may also offer components that can be used as biomarkers – for screening, diagnosis, monitoring disease recurrence and prognostic risk stratification of patients – and targets for localised analgesia offering less systemic side effects. This review summarises the current knowledge and potential for clinical opportunities related to the ET axis.